Violent Injuries Among College Students in China: An Exploration of Gender Mental Stress Model. Issue 3 (June 2020) - Yang, Tingzhong; Wang, Huihui; Zhang, Weifang; Fu, Jialu; Zhou, Huan; Yu, Lingwei; Peng, Sihui; Cottrell, Randall R.
The purpose of this study was to explore the gender-specific mental stress model of violent injuries among Chinese college students. A cross-sectional, multistage sampling process was employed to recruit a total of 5025 college students from 22 universities in China. Survey respondents reported their exposure to violent injuries and noted individual and environmental factors that could relate to violent injuries. Both unadjusted and adjusted statistical methods were used to examine the relationships between selected individual and environmental variables with violent injuries among male and female college students. The overall prevalence of violent injuries among male and female college students in this study was 4.40% (95% CI [0.10%, 7.80%]) and 5.20% (95% CI [0.05%, 10.35%]). The study found that higher mental stress (OR: 3.32), lower level universities (OR: 5.99), and family location in rural areas (OR: 4.00) were associated with a higher likelihood of violent injuries, and mothers employed as professionals (OR: 0.07) was associated with lower prevalence of violent injuries among male students. Unlike male students, mental stress and mothers' occupation were not associated with violent injuries among female students. University type was also associated with violent injuries but this association was inverted (OR: 0.06) among female students. This study found gender-specific relationships affecting violent injuries among college students in China. Prevention strategies need to be developed in consideration of gender influences and should be enacted to reduce the negative impact of violent injuries on society and personal health in China.